Single‐cell quantification of IL‐2 response by effector and regulatory T cells reveals critical plasticity in immune response - Ofer Feinerman; Garrit Jentsch; Karen E Tkach; Jesse W Coward; Matthew M Hathorn; Michael W Sneddon; Thierry Emonet; Kendall A Smith; Grégoire Altan‐Bonnet (Molecular Systems Biology, 2010)
Abstract Understanding how the immune system decides between tolerance and activation by antigens requires addressing cytokine regulation as a highly dynamic process. We quantified the dynamics of interleukin‐2 (IL‐2) signaling in a population of T cells during an immune response by combining in silico modeling and single‐cell measurements in vitro. We demonstrate that IL‐2 receptor expression levels vary widely among T cells creating a large variability in the ability of the individual cells to consume, produce and participate in IL‐2 signaling within the population. Our model reveals that at the population level, these heterogeneous cells are engaged in a tug‐of‐war for IL‐2 between regulatory (Treg) and effector (Teff) T cells, whereby access to IL‐2 can either increase the survival of Teff cells or the suppressive capacity of Treg cells. This tug‐of‐war is the mechanism enforcing, at the systems level, a core function of Treg cells, namely the specific suppression of survival signals for weakly activated Teff cells but not for strongly activated cells. Our integrated model yields quantitative, experimentally validated predictions for the manipulation of Treg suppression.